Magnetic Resonance with Marked T2-Weighted Images: Improved Demonstration of Brain Lesions, Tumor, and Edema - Smith, Alison S.; Weinstein, Meredith A.; Modic, Michael T.; Pavlicek, William; Rogers, Lisa R.; Budd, Thomas G.; Bukowski, Ronald M.; Purvis, Joseph D.; Weick, James K.; Duchesneau, Paul M. (American Journal of Neuroradiology, 1985)
The object of this study was to determine the sensitivity of magnetic resonance (MR) for imaging intracranial lesions with heavily T2-weighted images compared with that of computed tomographic (CT) and T1-weighted images. Fifty-five patients with known intracranial pathology consisting of primary neurogenic tumors, brain infarcts, demyelinating disease, and metastases were studied by MR and CT. Patients were studied with either 0.6 or 1.5 T systems with T1- and T2-weighted radiofrequency pulse sequences. The heavily T2-weighted images were found to be superior to the T1-weighted images in terms of sensitivity, with 168 lesions found versus 86 by CT and 104 by T1-weighted imaging.